Kötelek, zsinórok, hálók alkalmazása a bútortervezésben - Vass Martina (2017)
In my thesis I designed a furniture family for cafés and bars. The most important materials of these furnitures are cord and wood. First I collected information about the history of cord, the competitor furnitures and the ergonomic data. I made a function tree, then I chose the most important functions for a design guideline. I drew some furniture sketches, then we chose the best idea from them. I worked out this concept; I made a description, some design plans and technical drawings. I designed chairs, tables and bar stools. The speciality of this furnitures is the function to store handbags under the tabletop with the help of the rubber cord.